Chiral Macrocycle‐Enabled Counteranion Trapping for Boosting Highly Efficient and Enantioselective Catalysis. Issue 27 (3rd June 2020) - Ning, Rui; Zhou, Hao; Nie, Shi‐Xin; Ao, Yu‐Fei; Wang, De‐Xian; Wang, Qi‐Qiang
Abstract: The tight binding enabled by tailor‐made macrocycles can be manipulated for tuning the catalysis process. In parallel to well‐developed crown ether‐based cation‐binding catalysis, a macrocycle‐enabled counteranion trapping strategy is presented for boosting highly efficient and enantioselective catalysis. A set of bis‐diarylthiourea macrocycles containing two BINOL moieties were designed and synthesized. They possess a well‐confined chiral cavity and strong binding affinities towards disulfonate anions. Caused by the tight binding, just 1 mol % macrocycle in combination with 1 mol % ethanedisulfonic acid can promote excellent conversion and up to 99 % ee in the Friedel–Crafts reaction of indoles with imines. The acid or the macrocycle alone do not afford any reactivity. The high catalytic efficiency and excellent stereocontrol was ascribed to large, complexation‐induced acidity enhancement and tight ion‐pairing facilitated by cave‐like macrocyclic cavity. Abstract : Macrocycles in action : A chiral macrocycle‐enabled counteranion trapping strategy was demonstrated for boosting highly efficient and selective catalysis. Just 1 mol % of the designer macrocycle can promote excellent conversion and up to 99 % ee in combination with 1 mol % achiral acid, which is inactive alone.